Antiseizure medications for post‐stroke epilepsy: A real‐world prospective cohort study. Issue 9 (22nd August 2021) - Tanaka, Tomotaka; Fukuma, Kazuki; Abe, Soichiro; Matsubara, Soichiro; Motoyama, Rie; Mizobuchi, Masahiro; Yoshimura, Hajime; Matsuki, Takayuki; Manabe, Yasuhiro; Suzuki, Junichiro; Ikeda, Shuhei; Kamogawa, Naruhiko; et al.
Abstract: Background and purpose: The management of post‐stroke epilepsy (PSE) should ideally include prevention of both seizure and adverse effects; however, an optimal antiseizure medications (ASM) regimen has yet been established. The purpose of this study is to assess seizure recurrence, retention, and tolerability of older‐generation and newer‐generation ASM for PSE. Methods: This prospective multicenter cohort study (PROgnosis of Post‐Stroke Epilepsy [PROPOSE] study) was conducted from November 2014 to September 2019 at eight hospitals. A total of 372 patients admitted and treated with ASM at discharge were recruited. Due to the non‐interventional nature of the study, ASM regimen was not adjusted and followed standard hospital practices. The primary outcome was seizure recurrence in patients receiving older‐generation and newer‐generation ASM. The secondary outcomes were the retention and tolerability of ASM regimens. Results: Of the 372 PSE patients with ASM at discharge (median [IQR] age, 73 [64–81] years; 139 women [37.4%]), 36 were treated with older‐generation, 286 with newer‐generation, and 50 with mixed‐generation ASM. In older‐ and newer‐generation ASM groups ( n = 322), 98 patients (30.4%) had recurrent seizures and 91 patients (28.3%) switched ASM regimen during the follow‐up (371 [347–420] days). Seizure recurrence was lower in newer‐generation, compared with the older‐generation, ASM (hazard ratio [HR], 0.42, 95%CI 0.27–0.70; p = .0013). ASM regimen withdrawal and change of dosages were lower in newer‐generation ASM (HR, 0.34, 95% CI 0.21–0.56, p < .0001). Conclusions: Newer‐generation ASM possess advantages over older‐generation ASM for secondary prophylaxis of post‐stroke seizures in clinical practice. Abstract : The current study is a real‐world prospective cohort study to evaluate seizure control, retention, and tolerability of older or newer‐generation anti‐seizure medication (ASM) treatment in post‐stroke epilepsy (PSE). Seizure recurrence was lower in newer‐generation, compared with the older‐generation, ASM (hazard ratio [HR], 0.42, 95%CI 0.27–0.70; p = .0013). ASM regimen withdrawal and change of dosages were lower in newer‐generation ASM (HR, 0.34, 95% CI 0.21–0.56, p < .0001). These findings suggest potential for newer‐generation ASM as the primary choice in the secondary prophylaxis of PSE.